Metal-coated zirconia articles

Phosphate surface treatment of zirconia followed by metal deposition addresses the inefficiencies in coating zirconia substrates, resulting in strong metal adhesion and improved electrode performance.

JP2025501179APending Publication Date: 2025-01-17SOLVENTUM INTELLECTUAL PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024539277
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-28
Filing Date
2022-12-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing methods for coating zirconia substrates with conductive metals, such as silver, are inefficient and unsuitable for large-scale production, particularly for small zirconia particles, and result in poor adhesion, which is problematic for medical articles and electrodes.

Method used

A method involving phosphate surface treatment of zirconia followed by metal deposition, such as silver, using chemical or physical vapor deposition, enhances metal adhesion to the treated surface, suitable for producing metal-coated zirconia articles, especially for use in dry electrodes.

Benefits of technology

The method results in strong adhesion of metals to phosphate-treated zirconia surfaces, improving the performance and manufacturability of zirconia-based electrodes, particularly dry electrodes, by enhancing conductivity and reducing the need for hydrogel-based hydration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501179000001_ABST
    Figure 2025501179000001_ABST
Patent Text Reader

Abstract

The metal coated zirconia article has at least one surface which is a surface treated surface. The surface treated surface is a phosphate treated surface. At least a portion of the surface treated surface is coated with a layer of metal. The metal coating adheres more strongly to the surface treated surface than to the same surface that is not surface treated.
Need to check novelty before this filing date? Find Prior Art

Description

Summary of the Invention

[0001] SUMMARY OF THE DISCLOSURE Disclosed herein are metal-coated zirconia articles and methods for preparing metal-coated zirconia articles.

[0002] In some embodiments, a metal coated zirconia article comprises a zirconia-containing article having at least one major surface, at least a portion of which comprises a surface treated surface comprising a phosphate surface treated surface, and a layer of metal coating at least a portion of the surface treated surface, wherein the metal coating adheres more strongly to the surface treated surface than to the same surface that is not surface treated.

[0003] Similarly, methods for preparing metal coated zirconia articles are disclosed. In some embodiments, the method of preparing a metal coated article includes providing a zirconia-containing article having at least one major surface, surface treating at least a portion of at least one major surface of the article with a phosphate surface treatment to produce a phosphate treated surface, and disposing a layer of metal on at least a portion of the surface treated surface. [Brief description of the drawings]

[0004] The present application may be more fully understood in consideration of the following detailed description of various embodiments of the disclosure in conjunction with the accompanying drawings, in which: [Figure 1] FIG. 2 is a top view of a metal coated article of the present disclosure. [Diagram 2] FIG. 1 is a cross-sectional view of a dry electrode incorporating metal coated particles of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0005] In the following description of the illustrated embodiments, reference is made to the accompanying drawings, in which various embodiments in which the present disclosure may be practiced are shown by way of example. It is understood that the embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure. The drawings are not necessarily to scale. Like numbers used in the figures refer to like components. However, it will be understood that the use of a number to refer to a component in a given figure is not intended to limit the component in another figure labeled with the same number.

[0006] A wide range of articles can be prepared from zirconia. Examples of such articles are shaped non-compressed particles and a wide range of shaped articles. The shaped non-compressed particles are used in a wide range of applications. One recent application is the use of shaped non-compressed particles in electrodes. In this application, the particles are coated or at least partially coated with a conductive metal. Zirconia particles are difficult to coat with a conductive metal by conventional coating techniques.

[0007] One technique that has been explored for coating metals such as silver onto zirconia substrates is described in "Adhesion of Silver Films to Ion-Bombarded Zirconia", R.A. Erck and G.R.Fenske in Lubrication Engineering, 1991, Volume 47-8, pp. 640-644. In this report, the adhesion of the silver layer to the zirconia substrate is increased by using ion bombardment or a combination of ion bombardment and a thin intermediate layer of chromium or titanium. The use of these techniques is not suitable for large-scale production of metal-coated articles, and in particular the use of a chromium intermediate layer is problematic for medical articles designed to contact human skin. Furthermore, these techniques have difficulty or are unable to utilize small zirconia particles. Thus, there remains a need for a convenient, efficient, and cost-effective method for preparing zirconia-containing articles, especially particles, with a metal coating. Such a method for preparing metal-coated zirconia particles is disclosed herein.

[0008] As mentioned above, non-compressed particles, especially metal-coated non-compressed particles, are useful in a wide range of applications, especially electrodes. Among the electrodes in which such particles have been found to be particularly useful are so-called "dry electrodes", as described, for example, in PCT Publication No. 2020 / 099965.

[0009] Electrodes for measuring biopotentials are widely used in modern clinical and biomedical applications, including a number of physiological tests, including electrocardiography (ECG), electroencephalography (EEG), electrical impedance tomography (EIT), electromyography (EMG) and electrooculography (EOG). Electrodes for these types of physiological tests act as transducers by converting electrical potentials in the body, or biopotentials, into voltages that can be measured by conventional measuring and recording devices.

[0010] Generally, such electrodes are attached to the surface of the skin. The challenge with electrodes placed on the surface of the skin is that the outer layer of the skin, the stratum corneum, lacks moisture, which results in high impedance. This high impedance is due to the lack of ion mobility due to the lack of moisture in the stratum corneum.

[0011] Electrical conduction in the body is based on the movement of ions, rather than the movement of electrons as found in metallic conductors. In order to record electronic signals from the body, electrodes must convert ionic conduction to electronic conduction. The majority of electrodes available today achieve this conversion through the use of a silver / silver chloride reduction / oxidation reaction. Ag adjacent to the skin + and Cl - The ion-containing hydrogel provides wetting of the stratum corneum and allows ion transfer between the skin and the electrode. The conversion takes place within the electrode at the interface of the hydrogel and a conductive material (usually a metal snap or a layer of conductive carbon composite). The conductive material is coated with silver, allowing the following reversible reaction, thus allowing the detection of electrical pulses in the body:

[0012] [ka]

[0013] One of the challenges with the use of hydrogel-containing electrodes is that the water in the hydrogel is prone to evaporation. Thus, upon use, the hydrogel may lose water and become ineffective. Furthermore, loss of water from the hydrogel when the electrodes are stored and transported is a significant issue. To prevent water loss from the hydrogel prior to its use, expensive packaging, such as foil-lined envelopes, is often used to extend the limited shelf life of such electrodes.

[0014] Therefore, much effort has been spent on developing "dry" electrodes that do not utilize hydrogels. To create dry electrodes, many attempts have focused on alternatives to using hydrogels to hydrate the dry stratum corneum, which is to use small structures to penetrate the stratum corneum and access the more watery layers of the skin below. Typically, the structures are coated with a material that forms a reduction / oxidation pair (usually silver and silver chloride) in the presence of moisture. Examples of such small structures that have been used include microneedles or similar small pointed structures to penetrate the stratum corneum and reach deeper layers of the skin that have more moisture and where ions are more mobile, thereby enabling conduction.

[0015] The methods of manufacturing these electrodes usually involve injection molding or other similar processes, followed by coating the formed microneedle structures with redox couples, which is a labor-intensive and relatively costly process. These manufacturing issues have limited dry electrodes to a niche market. Thus, new processes are needed to prepare dry electrodes in an economical way that allows these electrodes to compete in the market with the relatively easily manufactured wet electrodes.

[0016] In the present disclosure, articles are described that include metal-coated zirconia-containing articles, which comprise a phosphate-treated surface with a metal coating on the treated surface. The metal adheres more strongly to the treated surface than to the same non-treated surface. In many embodiments, the metal-coated articles include shaped, non-compressed particles that contain zirconia. Also disclosed are methods of preparing these metal-coated articles, particularly metal-coated shaped, non-compressed particles suitable for use in the manufacture of dry electrodes.

[0017] As used herein, the terms "shaped abrasive particles" and "shaped particles" are used interchangeably and refer to ceramic particles that can be used as abrasive particles, where at least a portion of the particle has a predetermined shape that is replicated from the mold cavity used to form the shaped precursor particles. Shaped particles generally have a predetermined geometric shape that substantially replicates the mold cavity used to form the shaped particles. As used herein, shaped particles exclude abrasive particles obtained by mechanical grinding operations.

[0018] As used herein, the term "incompressible" when referring to particles refers to non-porous ceramic particles having a compressive strength of greater than 400 MPa (megapascals). In some embodiments, the particles have a compressive strength of greater than 600 MPa, 800 MPa, 1 GPa, or even 2 GPa.

[0019] The terms "room temperature" and "ambient temperature" are used interchangeably to mean a temperature in the range of 20°C to 25°C.

[0020] The term "adjacent" as used herein when referring to two layers means that the two layers are close to each other with no intervening open space between them. They may be in direct contact with each other (e.g., laminated together) or there may be an intervening layer.

[0021] The term "zirconia-based" refers to particles or articles that may include only zirconia (i.e., zirconium oxide) or may optionally include other materials such as other metal oxides. If they contain other materials, the zirconia is present in an amount of at least 50% by weight, more typically at least 70% by weight. As used herein, the term "zirconia-containing" refers to articles that are zirconia-based.

[0022] Disclosed herein is a metal-coated article, including a zirconia-containing article having at least one major surface, at least a portion of which comprises a surface-treated surface comprising a phosphate-surface-treated surface, and a layer of metal coating at least a portion of the surface-treated surface, wherein the metal coating adheres more strongly to the surface-treated surface than to the same surface that is not surface-treated.

[0023] A wide range of metal-coated zirconia-containing articles are suitable. In many embodiments, the zirconia-containing articles include non-compression-formed zirconia-containing particles. Although a wide range of non-compression-formed zirconia-containing particles are suitable, in many embodiments, the non-compression-formed zirconia-containing particles include at least one dot. Examples of suitable particles include particles prepared by the method used to make shaped abrasive particles, and the particles can have a wide range of shapes, including shapes such as caltrops. The particles are non-compressible, which means that the particles have a compressive strength of more than 400 MPa, 600 MPa, 800 MPa, 1 GPa, or even 2 GPa.

[0024] Although a wide range of sizes and shapes are suitable for the shaped particles, the shaped particles have at least one dimension between 175 and 1,500 micrometers, in some embodiments, the shaped particles have at least one dimension between 175 and 750 micrometers, or even between 200 and 600 micrometers.

[0025] In some embodiments, the non-compressed shaped particles include ceramic shaped particles. An example of a suitable ceramic shaped particle is a shaped abrasive particle with sloping sidewalls, as described in U.S. Pat. No. 8,142,531. The process of making shaped particles is known in the art. Shaped abrasive particles are particularly desirable for use in forming the articles of the present disclosure, as they can be mass-produced using known techniques, as described below, and can be coated with a conductive coating material to form particles with at least one point. These pointed conductive particles, when formed into a dry electrode, are non-compressible and can penetrate the stratum corneum.

[0026] The formation of zirconia-containing shaped particles is described, for example, in PCT Publication No. 2016 / 140840 and U.S. Patent Nos. 9,878,954 and 10,550,627. The multi-step process for forming the zirconia-containing shaped particles is briefly summarized below.

[0027] Typically, a method of making zirconia-containing particles includes the steps of: (a) providing a mold having a mold cavity; (b) disposing a reaction mixture in the mold cavity; (c) polymerizing the reaction mixture to form a shaped gel body in contact with the mold cavity; (d) removing the shaped gel body from the mold cavity, wherein the shaped gel body retains substantially the same size and shape as the mold cavity; (e) removing the solvent medium to form a dried shaped gel body; and (f) heating the dried shaped gel body to form a sintered body.

[0028] The reaction mixture used to form the molded gel article includes (a) zirconia-based particles, (b) a solvent medium including an organic solvent having a boiling point at least equal to 150° C., (c) a polymerizable material including a first surface modifier having free radical polymerizable groups, and (d) a photoinitiator for the free radical polymerization reaction.

[0029] As mentioned above, the zirconia-based particles may include other metal oxide particles than zirconium oxide particles. Up to 30 mole percent of the zirconia-based particles can be Y2O3, La2O3, Al2O3, CeO2, Pr2O3, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Fe2O3, MnO2, Co2O3, Cr2O3, NiO, CuO, V2O3, Bi2O3, Ga2O3, Lu2O3, HfO2, or mixtures thereof.

[0030] The solvent medium may contain water and also contains at least 60% by weight of an organic solvent having a boiling point at least equal to 150° C. In some embodiments, the solvent medium contains at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 97% by weight, at least 98% by weight, or at least 99% by weight of an organic solvent having a boiling point at least equal to 150° C.

[0031] The organic solvent is often a glycol or polyglycol, a monoether glycol or polyglycol, a diether glycol or polyglycol, an ether ester glycol or polyglycol, a carbonate, an amide, or a sulfoxide (e.g., dimethyl sulfoxide). The organic solvent usually has one or more polar groups. The organic solvent does not have a polymerizable group. That is, the organic solvent does not contain a group that can undergo free radical polymerization. Furthermore, the components of the solvent medium do not have a polymerizable group that can undergo free radical polymerization.

[0032] The reaction mixture includes one or more polymerizable materials having polymerizable groups capable of undergoing free radical polymerization (i.e., the polymerizable groups are free radically polymerizable). In many embodiments, the polymerizable groups have the formula: -(CO)-CR b is an ethylenically unsaturated group such as a (meth)acryloyl group, which is a group of =CH2, b is hydrogen or methyl. In some embodiments, the polymerizable group is a vinyl group (-CH=CH2) that is not a (meth)acryloyl group. The polymerizable material is typically selected to be soluble or miscible in an organic solvent having a boiling point at least equal to 150°C.

[0033] The reaction mixture used to form the gel composition contains a photoinitiator. The reaction mixture is advantageously initiated by the application of actinic radiation; that is, the polymerizable material is polymerized using a photoinitiator rather than a thermal initiator. Surprisingly, the use of a photoinitiator rather than a thermal initiator tends to result in a more uniform cure throughout the gel composition, ensuring uniform shrinkage in subsequent steps involved in forming the sintered article. Additionally, the outer surface of the cured part is more uniform and has fewer defects when a photoinitiator rather than a thermal initiator is used.

[0034] A wide range of photoinitiators are known in the art. Some exemplary photoinitiators are benzoin ethers (e.g., benzoin methyl ether or benzoin isopropyl ether) or substituted benzoin ethers (e.g., anisoin methyl ether). Examples of suitable commercially available photoinitiators include IRGACURE651, ESACURE KB-1, IRGACURE184, IRGACURE819, IRGACURE2959, IRGACURE369, IRGACURE907 and DAROCUR1173.

[0035] Polymerization of the reaction mixture occurs upon exposure to ultraviolet and / or visible light, resulting in the formation of a gel composition that is a polymerized (cured) product of the reaction mixture. The gel composition is a molded gel article having the same shape as the mold (e.g., mold cavity). The gel composition is a solid or semi-solid matrix with a liquid trapped within it. The solvent medium in the gel composition is primarily an organic solvent having a boiling point at least equal to 150° C. The molded gel article is stable and has sufficient strength to withstand drying and sintering.

[0036] After polymerization, the shaped gel article is removed from the mold cavity and treated to remove the organic solvent having a boiling point at least equal to 150° C. and any other organic solvents or water that may be present. This may be referred to as drying the gel composition or shaped gel article, regardless of the method used to remove the organic solvent. Any desired drying temperature up to 200° C. may be used. A xerogel results from such a process of organic solvent removal.

[0037] After removal of the solvent medium, the resulting xerogel is heated to remove any polymeric or other organic material that may be present and to build strength by densification. Temperatures are often raised as high as 1000° C. or 1100° C. during this process. This process is commonly referred to as "organic combustion."

[0038] After organic combustion, the article is sintered. Sintering is typically performed at a temperature higher than 1100°C, such as, for example, at least 1200°C, at least 1250°C, at least 1300°C, or at least 1320°C. The heating rate can be very rapid, such as at least 100°C / hr, at least 200°C / hr, at least 400°C / hr, or at least 600°C / hr. The temperature can be held for any desired time to produce a sintered article with a desired density. In some embodiments, the temperature is held for at least 1 hour, at least 2 hours, or at least 4 hours. The temperature can be held for 24 hours or even longer, if desired.

[0039] The resulting particles are non-porous crystalline particles having a density that is at least 98.5, 99, 99.5, 99.9 or even 99.99% of the theoretical density.

[0040] As mentioned above, the zirconia-containing article is surface treated to enhance the adhesion of metals to the surface of the zirconia-containing article. This surface treatment is a phosphate surface treatment. The surface treatment may be applied to the entire surface of the zirconia-containing article or may be applied to only a portion of the zirconia-containing article, so long as the portion of the zirconia-containing article that will be coated with metal is surface treated.

[0041] The surface treatment is a phosphate surface treatment, meaning that the surface treatment agent is a phosphate. The surface treatment is carried out by surface treating the surface of the zirconia-containing article with a solution of phosphoric acid, a phosphate, or a combination thereof. Examples of phosphates include, for example, sodium phosphate, potassium phosphate, and ammonium phosphate. The surface treatment may be carried out by immersing the article in the surface treatment solution, or the surface treatment solution may be applied to the article surface. Typically, after applying the surface treatment solution, the surface of the article is rinsed with water or an aqueous solution to remove excess surface treatment agent. After rinsing, the article may be dried either by air drying or by application of heat, for example by placing the article in an oven.

[0042] The metal-coated articles of the present disclosure also contain a metal coating. The coating may cover the entire zirconia-containing article, or more typically, may cover only a portion of the zirconia-containing article. Examples of suitable metals include silver, copper, zinc, gold, aluminum, iron, or nickel, or alloys thereof. Typically, the metal coating is electrically conductive, especially in embodiments where the article is to be used as an electrode. Although a range of conductive metals are possible, silver is a particularly preferred metal. A wide range of thicknesses are suitable. Typically, the metal coating has a thickness of 20 nanometers to 2 micrometers.

[0043] A wide variety of methods can be used to apply the metal coating to the surface treated article, including chemical deposition, vapor deposition, or a combination of methods.

[0044] In some embodiments, the metal coating is produced by chemical deposition. Chemical deposition can be performed in a variety of ways. In some embodiments, a metal salt is deposited on the surface of the surface-treated article, and the metal coating is then formed by thermal reduction of the metal salt. In this method, the surface-treated article is typically immersed in a solution of a metal salt, such as AgNO3. The article is removed from the metal salt solution, optionally rinsed and / or dried, and can be heated to an elevated temperature to induce thermal reduction of the metal salt on the surface. In the example of AgNO3, the article can be heated to a temperature of 400°C for 30 minutes.

[0045] In another variation, the method of disposing a layer of metal on at least a portion of the surface-treated surface includes depositing the metal from a metal solution by a chemical reduction reaction. When the metal is silver, the chemical reduction can be carried out using the Tollens reaction. The Tollens reaction is a mechanism for the Tollens test for aldehydes, also known as the silver mirror test. This test involves determining whether a solution contains an aldehyde by contacting the solution with a solution containing silver(I) ions. The aldehyde is Ag. + ions to silver metal, which itself is oxidized to a carboxylic acid. If this test is performed in the presence of a surface-treated surface, the silver metal forms a layer on the surface.

[0046] In some embodiments, the metal layer is disposed on the surface of a zirconium-containing article that has been surface-treated by PVD (physical vapor deposition). Examples of suitable PVD methods include sputter coating and other vapor deposition techniques, such as those described in U.S. Patent No. 8,664,149. These processes are well understood in the art and can produce coatings having a wide range of thicknesses.

[0047] As mentioned above, in some embodiments, the metal-coated shaped particles can be used as electrodes. In these embodiments, additional steps can be implemented to facilitate the use of the article as an electrode. In some embodiments, the conductive metal coating can be a multi-layer coating, for example, the conductive metal coating can cover the entire surface or substantially the entire surface of the shaped particle, and a secondary coating, such as a silver coating or a silver / silver chloride coating, can be selectively coated on all or part of the first conductive metal coating. In some embodiments, the metal-coated particles include particles completely coated with silver, and a portion of this coating can be converted to a silver / silver chloride coating, or a portion of the silver coating can be overcoated with a silver chloride coating.

[0048] Also disclosed herein is a method of preparing a metal coated article. In some embodiments, the method includes providing a zirconia-containing article having at least one major surface, surface treating at least a portion of the at least one major surface of the article with a phosphate surface treatment to produce a phosphate-treated surface, and disposing a layer of metal on at least a portion of the surface-treated surface.

[0049] Suitable zirconia-containing articles, methods of surface treatment, and methods of disposing a layer of metal on a surface-treated surface are described above. As noted above, in some embodiments, the zirconium-containing article comprises non-compressed shaped zirconia-containing particles, typically particles that include at least one dot, having at least one dimension of 175 to 1,500 micrometers. In some embodiments, at least one dimension of the shaped particles is 175 to 750 micrometers, or even 200 to 600 micrometers. While a wide range of metals are suitable, in many embodiments the metal comprises silver and the metal coating is electrically conductive.

[0050] This disclosure may be more fully understood from the drawings. In Figure 1, article 100 is a non-compressed molded zirconia-containing particle. The particle has a phosphate surface treatment layer 110 and a metal coating layer 120. In this embodiment, the phosphate surface treatment layer 110 is shown covering the entire surface of the article 100, and the metal coating layer 120 is shown covering only a portion of the phosphate surface treatment layer 110.

[0051] Figure 2 shows one embodiment of a dry electrode utilizing metal coated non-compressed zirconia-containing particles of the present disclosure. In Figure 2, dry electrode 200 has conductive particles 201 and a support layer 230 having three sublayers 231, 232, 233, where 231 and 233 are adhesive layers and 232 is a film layer. Layer 240 is a conductive substrate including conductive layer 241 and optional film layer 242. Electrical connector 250 is in electrical contact with conductive substrate 240. EXAMPLES

[0052] These examples are for illustrative purposes only and are not meant to limit the scope of the appended claims. All parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight unless otherwise noted. The following abbreviations are used: cm = centimeters; in = inches; mm = millimeters; sccm = standard cubic centimeters per minute. The terms "weight %", "% by weight" and "wt %" are used interchangeably.

[0053] Test Method Silver layer adhesion test The adhesion of the silver layer deposited on the zirconia surface was tested using tape. The tape was applied and pressed down with hand pressure to adhere the tape to the silver-deposited surface. The tape was then removed and the amount of silver removed was recorded. Three tapes selected for different levels of adhesion were used for the test: SCOTCH #600 transparent tape adhesive, 3M 8403HD adhesive, and POST-IT Note (all products of 3M Company, St. Paul, Minn.).

[0054] Explanation of the Tollens reaction The Tollenz reaction works by the reduction of silver ions by an aldehyde. In the solution used in this procedure, the silver ions are obtained by dissolving silver nitrate in an aqueous solution containing ammonium hydroxide. The solution is then stirred until all the silver nitrate has dissolved and is clear again. The reducing agent in this experiment (the aldehyde) is obtained by dissolving sugar in water. When the two solutions are added together, the aldehyde is oxidized by the Tollenz solution to form a carboxylate. The carboxylate is then reduced by the positive silver ions and solid silver is formed in the solution.

[0055] Working Example A. Example of the Tollen reaction Example 1 and Comparative Example CE1: Zirconia disk Example 1: Treatment of zirconia disks with phosphoric acid a. Surface treatment of zirconia disc: Sintered zirconia disks were coated with dental phosphoric acid (SCOTCHBOND Universal Etchant, 3M) and rinsed with deionized (DI) water after 30 seconds. The disks were dried and then immersed in AgNO3 solution (Alfa Aesar, Haverhill, MA) overnight. The disks were then placed in a BLUE-M furnace and dried at 80°C. After drying, the disks were heated to 400°C in a THERMOLYNE 1200 (VWR International, LLC, Radnor, PA) to induce thermal reduction of AgNO3 to Ag. A slight color change of the disk surface was observed. The treated disks (Example 1) were further treated using the Tollens reaction.

[0056] Comparative Example CE1: Zirconia disc with no surface treatment a. Surface treatment of zirconia disc: In the case of Comparative Example CE1, no surface treatment was performed. An untreated disk (Comparative Example CE1) was further treated using the Tollens reaction.

[0057] b. Formation of a silver layer by Tollens reaction: A conductive silver seed layer was deposited on each surface using the Tollenth reaction. The disks were immersed in an aqueous solution of 0.58 wt% silver nitrate (AgNO3 crystals, RQ, Ames Goldsmith, Elkton, Maryland), 1.18 wt% ammonium hydroxide (VWR ACS grade ammonium hydroxide, 28-30%, Radnor, Pennsylvania), and 0.26 wt% potassium hydroxide (≥85% pellets, Honeywell, Charlotte, North Carolina), also called the Tollenth solution. While the Tollenth solution was stirred with a stir bar, a sugar solution (dextrose, anhydrous ACS grade, EMD Millipore, Burlington, Massachusetts) was slowly added to the beaker. The Tollenth solution and sugar solution were allowed to react until a visual color change was observed in the beaker, indicating that all available silver nitrate had been converted to pure silver.

[0058] c. Silver layer adhesion test The disks were tested for silver adhesion using the Silver Layer Adhesion Test described above.

[0059] Results for Example 1: No visible silver was removed by any of the test tapes.

[0060] Comparative Example CE1 Results: A large amount of silver was removed by SCOTCH #600 and 3M 8403HD adhesive tape.

[0061] Example 2: Zirconia scalloped tetrahedral particles treated with phosphoric acid: a. Treatment of Zirconia Scalloped Tetrahedral Particles: Dental phosphoric acid was diluted with DI water (0.5 g dental etching gel + 25.28 g DI water). The zirconia particles were placed in a 20 micrometer polymeric screen material, the screen containing the particles was placed in a bottle, the bottle was closed, and the bottle was immersed in acid for about 10 minutes with agitation by immersing the bottle in an ultrasonic bath. The particles were rinsed with distilled water until the blue color from the dental etch was washed off. While still wet, the particles were placed in an AgNO3 solution (1.23 g AgNO3 + 25.52 g DI water) for about 10 minutes, while simultaneously being placed in a bottle and agitated by immersing the closed bottle in an ultrasonic bath for about 10 minutes.

[0062] The screen containing the particles was removed from the bottle and placed in a Blue-M furnace at 80°C to dry. After drying, the particles showed a relatively uniform brown appearance. The dried particles were removed from the screen and placed in a porcelain crucible. The crucible was placed in a THERMOLYNE 1200 and heat treated by heating to 440°C at 20°C / min, holding at 440°C for 30 minutes, and then allowed to cool naturally in the furnace by turning off the power. After heat treatment, the particles appeared slightly grey. Optical microscope images showed small silver droplets on the surfaces of the tetrahedrons.

[0063] Example 3: Treatment of zirconia discs with potassium phosphate a. Surface treatment of zirconia disc: 1.03 g of potassium monophosphate (KH2PO4, Millipore-Sigma, St. Louis, MO, USA) was dissolved in 25.26 g of distilled water. Zirconia disks were immersed in the solution for 30 seconds, pat-dried with a Kimwipe, rinsed with distilled water, and dried in a BLUE-M Box Oven at 80° C. The treated disks were further processed using the Tollens reaction.

[0064] b. Formation of a silver layer by Tollens reaction: A conductive silver seed layer was deposited on each surface using the Tollenth reaction. The disks were immersed in an aqueous solution of 0.58 wt% silver nitrate (AgNO3 crystals, RQ, Ames Goldsmith, Elkton, Maryland), 1.18 wt% ammonium hydroxide (VWR ACS grade ammonium hydroxide, 28-30% (Radnor, Pennsylvania)), and 0.26 wt% potassium hydroxide (≥85% pellets, Honeywell, Charlotte, North Carolina), also called the Tollenth solution. While the Tollenth solution was stirred with a stir bar, a sugar solution (dextrose, anhydrous ACS grade, EMD Millipore, Burlington, Massachusetts) was slowly added to the beaker. The Tollenth solution and sugar solution were allowed to react until a visual color change was observed in the beaker, indicating that all available silver nitrate had been converted to pure silver.

[0065] c. Silver layer adhesion test The disks were tested for silver adhesion using the Silver Layer Adhesion Test described above.

[0066] Results for Example 3: A small amount of silver was removed by the SCOTCH #600 adhesive tape and no silver was removed by the other two adhesives.

[0067] Example 4: Treatment of zirconia discs with sodium phosphate a. Surface treatment of zirconia disc: 1.01 g of sodium phosphate (NaH2PO4, Millipore-Sigma, St. Louis, MO, USA) was dissolved in 25.1 g of distilled water. The zirconia disk was immersed in the solution for 30 seconds, patted dry with a Kimwipe, rinsed with distilled water, and dried in a BLUE-M Box Oven at 80 °C.

[0068] b. Formation of a silver layer by Tollens reaction: A conductive silver seed layer was deposited on the surface using the Tollenth reaction. The disk was immersed in an aqueous solution of 0.58 wt% silver nitrate (AgNO3 crystals, RQ, Ames Goldsmith, Elkton, Maryland), 1.18 wt% ammonium hydroxide (VWR ACS grade ammonium hydroxide, 28-30% (Radnor, Pennsylvania)), and 0.26 wt% potassium hydroxide (≥85% pellets, Honeywell, Charlotte, North Carolina), also called the Tollenth solution. While the Tollenth solution was stirred with a stir bar, a sugar solution (dextrose, anhydrous ACS grade, EMD Millipore, Burlington, Massachusetts) was slowly added to the beaker. The Tollenth solution and sugar solution were allowed to react until a visual color change was observed in the beaker, indicating that all available silver nitrate had been converted to pure silver.

[0069] c. Silver layer adhesion test The disks were tested for silver adhesion using the Silver Layer Adhesion Test described above.

[0070] Results for Example 4: None of the three adhesives removed any visible silver.

[0071] B. PVD Examples Comparative Example CE2: Zirconia disc a. Surface treatment of zirconia disc: Yttria-stabilized zirconia disks approximately 10 mm square were washed in isopropanol (IPA) and placed in an oven at 150° C. overnight to remove any water on the surface. No surface treatment was performed.

[0072] b. Formation of a silver layer by PVD sputtering: The zirconia substrate was placed on a specially modified plate in a cylindrical sputtering vacuum chamber. The plate was attached to a Keithly 247 2000 volt power supply via a BNC feedthrough in the chamber wall. The plate was insulated from the grounded chamber by a 3 inch diameter by 0.25 inch thick (8 cm by 0.6 cm) plate of PTFE (polytetrafluoroethylene). A circular 3 inch by 0.25 inch thick (8 cm by 0.6 cm) Ag sputtering target (99.99% purity, Kurt J Lesker Co.) was used as the silver material source. The sputtering source was oriented at approximately 30 degrees perpendicular to the substrate. The sputtering source was within approximately 8 inches (20 cm) of the substrate. The 3.8×10 -6 After pumping down to a base pressure of 100 Torr (ion gauge), argon gas (99.999% ultra-high purity) was introduced into the vacuum chamber using an MKS246 flow controller at a flow rate of 100 sccm. A manual gate valve was used as a throttle valve to maintain the process pressure of the vacuum chamber at 10 mTorr. 1.0 kilowatts was applied to the Ag sputter target for 30 seconds. The Ag-coated zirconia disk was removed from the chamber.

[0073] c. Silver layer adhesion test The disks were tested for silver adhesion using the Silver Layer Adhesion Test described above.

[0074] Results for Comparative Example CE2: 3M 8403HD adhesive removes a lot of silver, SCOTCH#600 adhesive removes a little silver, and POST-IT adhesive removes no silver.

[0075] Example 5: Treatment of zirconia disks with phosphoric acid a. Surface treatment of zirconia disc: Yttria-stabilized zirconia disks approximately 10 mm square were washed in isopropanol (IPA) and placed in an oven at 150° C. overnight to remove any water on the surface. The disks were coated with dental phosphoric acid (SCOTCHBOND Universal Etchant, 3M) and rinsed with deionized (DI) water after 30 seconds.

[0076] b. Formation of a silver layer by PVD sputtering: The zirconia substrate was placed on a specially modified plate in a cylindrical sputtering vacuum chamber. The plate was attached to a Keithly 247 2000 volt power supply via a BNC feedthrough in the chamber wall. The plate was insulated from the grounded chamber by a 3 inch diameter by 0.25 inch thick (8 cm by 0.6 cm) plate of PTFE (polytetrafluoroethylene). A circular 3 inch by 0.25 inch thick (8 cm by 0.6 cm) Ag sputtering target (99.99% purity, Kurt J Lesker Co.) was used as the silver material source. The sputtering source was oriented at approximately 30 degrees perpendicular to the substrate. The sputtering source was within approximately 8 inches (20 cm) of the substrate. The 3.8×10 -6 After pumping down to a base pressure of 100 Torr (ion gauge), argon gas (99.999% ultra-high purity) was introduced into the vacuum chamber using an MKS246 flow controller at a flow rate of 100 sccm. A manual gate valve was used as a throttle valve to maintain the process pressure of the vacuum chamber at 10 mTorr. 1.0 kilowatts was applied to the Ag sputter target for 30 seconds. The Ag-coated zirconia disk was removed from the chamber.

[0077] c. Silver layer adhesion test The disks were tested for silver adhesion using the Silver Layer Adhesion Test described above.

[0078] Results for Example 5: None of the three adhesives removed any visible silver.

[0079] Example 6: Treatment of zirconia disks with potassium phosphate a. Surface treatment of zirconia disc: A yttria-stabilized zirconia disk approximately 10 mm square was washed in isopropanol (IPA) and placed in an oven at 150°C overnight to remove any water on the surface. 1.03 g of potassium monophosphate (KH2PO4, Millipore-Sigma, St. Louis, MO, USA) was dissolved in 25.26 g of distilled water. The zirconia disk was immersed in the solution for 30 seconds, patted dry with a Kimwipe, rinsed with distilled water, and dried in a BLUE-M Box Oven at 80°C.

[0080] b. Formation of a silver layer by PVD sputtering: The zirconia substrate was placed on a specially modified plate in a cylindrical sputtering vacuum chamber. The plate was attached to a Keithly 247 2000 volt power supply via a BNC feedthrough in the chamber wall. The plate was insulated from the grounded chamber by a 3 inch diameter by 0.25 inch thick (8 cm by 0.6 cm) plate of PTFE (polytetrafluoroethylene). A circular 3 inch by 0.25 inch thick (8 cm by 0.6 cm) Ag sputtering target (99.99% purity, Kurt J Lesker Co.) was used as the silver material source. The sputtering source was oriented at approximately 30 degrees perpendicular to the substrate. The sputtering source was within approximately 8 inches (20 cm) of the substrate. The 3.8×10 -6 After pumping down to a base pressure of 100 Torr (ion gauge), argon gas (99.999% ultra-high purity) was introduced into the vacuum chamber using an MKS246 flow controller at a flow rate of 100 sccm. A manual gate valve was used as a throttle valve to maintain the process pressure of the vacuum chamber at 10 mTorr. 1.0 kilowatts was applied to the Ag sputter target for 30 seconds. The Ag-coated zirconia disk was removed from the chamber.

[0081] c. Silver layer adhesion test The disks were tested for silver adhesion using the Silver Layer Adhesion Test described above.

[0082] Results of Example 6: After removal, a small amount of silver can be observed on the 3M 8403HD adhesive. No silver was removed by the other two adhesives.

[0083] Example 7: Treatment of zirconia discs with sodium phosphate a. Surface treatment of zirconia disc: A yttria-stabilized zirconia disk approximately 10 mm square was washed in isopropanol (IPA) and placed in an oven at 150°C overnight to remove any water on the surface. 1.01 g of sodium phosphate (NaH2PO4, Millipore-Sigma, St. Louis, MO, USA) was dissolved in 25.1 g of distilled water. The zirconia disk was immersed in the solution for 30 seconds, patted dry with a Kimwipe, rinsed with distilled water, and dried in a BLUE-M Box Oven at 80°C.

[0084] b. Formation of a silver layer by PVD sputtering: The zirconia substrate was placed on a specially modified plate in a cylindrical sputtering vacuum chamber. The plate was attached to a Keithly 247 2000 volt power supply via a BNC feedthrough in the chamber wall. The plate was insulated from the grounded chamber by a 3 inch diameter by 0.25 inch thick (8 cm by 0.6 cm) plate of PTFE (polytetrafluoroethylene). A circular 3 inch by 0.25 inch thick (8 cm by 0.6 cm) Ag sputtering target (99.99% purity, Kurt J Lesker Co.) was used as the silver material source. The sputtering source was oriented at approximately 30 degrees perpendicular to the substrate. The sputtering source was within approximately 8 inches (20 cm) of the substrate. The 3.8×10 -6After pumping down to a base pressure of 100 Torr (ion gauge), argon gas (99.999% ultra-high purity) was introduced into the vacuum chamber using an MKS246 flow controller at a flow rate of 100 sccm. A manual gate valve was used as a throttle valve to maintain the process pressure of the vacuum chamber at 10 mTorr. 1.0 kilowatts was applied to the Ag sputter target for 30 seconds. The Ag-coated zirconia disk was removed from the chamber.

[0085] c. Silver layer adhesion test The disks were tested for silver adhesion using the Silver Layer Adhesion Test described above.

[0086] Results for Example 7: A large amount of silver was removed by the SCOTCH #600 adhesive. No silver was removed by the other two adhesives.

Claims

1. 1. A metal coated article comprising: a zirconia-containing article having at least one major surface, at least a portion of said surface comprising a surface treated surface comprising a phosphate surface treated surface; a layer of metal covering at least a portion of the surface-treated surface, the metal covering adhering more strongly to the surface-treated surface than to an identical surface that is not surface-treated; and The metal coated article comprising:

2. The metal coated article of claim 1 , wherein the zirconia-containing article comprises non-compressed zirconia-containing particles.

3. The metal coated article of claim 2 , wherein the uncompressed zirconia-containing particles include at least one dot.

4. The metal coated article of claim 3, wherein the uncompressed zirconia-containing particles have at least one dimension ranging from 175 to 1,500 micrometers.

5. 10. The metal coated article of claim 1, wherein the metal comprises silver, copper, zinc, gold, aluminum, iron or nickel, or an alloy thereof.

6. 10. The metal coated article of claim 1, wherein the metal coating has a thickness of from 20 nanometers to 2 micrometers.

7. The metal coated article of claim 1 , wherein the metal coating is electrically conductive.

8. The metal coated article of claim 1 comprising an electrode.

9. 1. A method for preparing a metal coated article, comprising: Providing a zirconia-containing article having at least one major surface; surface treating at least a portion of the at least one major surface of the article with a phosphate surface treatment to produce a phosphate treated surface; providing a layer of metal on at least a portion of the surface-treated surface; The method comprising:

10. 10. The method of claim 9, wherein the metal comprises silver, copper, zinc, gold, aluminum, iron or nickel, or an alloy thereof.

11. 10. The method of claim 9, wherein the surface treating step comprises treating the zirconia-containing surface with a solution of phosphoric acid, a phosphate salt, or a combination thereof.

12. 10. The method of claim 9, wherein the step of providing a layer of metal on at least a portion of the surface-treated surface comprises depositing a metal from a metal solution by a chemical reduction reaction.

13. 13. The method of claim 12, wherein the metal comprises silver and the deposition of a metal from a metal solution is a Tollens reaction.

14. 13. The method of claim 12, wherein the metal comprises silver and the deposition of the metal from a metal solution is a thermal reduction process.

15. The method of claim 9 , wherein providing a layer of metal on at least a portion of the surface-treated surface comprises a sputtering or vapor deposition process.

16. The method of claim 9 , wherein the zirconia-containing article comprises non-compressed zirconia-containing particles.

17. The method of claim 16 , wherein the uncompacted zirconia-containing particles include at least one point.

18. The method of claim 17, wherein the uncompressed zirconia-containing particles have at least one dimension ranging from 175 to 1,500 micrometers.

19. The method of claim 9 , wherein the metal coating is electrically conductive.